2020
DOI: 10.3390/genes11050499
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Intra-Tumoral Heterogeneity and Clonal Evolution in NF1-MPNST

Abstract: Sarcomas are highly aggressive cancers that have a high propensity for metastasis, fail to respond to conventional therapies, and carry a poor 5-year survival rate. This is particularly true for patients with neurofibromatosis type 1 (NF1), in which 8%–13% of affected individuals will develop a malignant peripheral nerve sheath tumor (MPNST). Despite continued research, no effective therapies have emerged from recent clinical trials based on preclinical work. One explanation for these failures could be the lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…Moon and Tompkins et al performed a comprehensive genomic analysis of multiple areas from within a single large MPNST. These authors identify varied genomic profiles within each area, highlighting the need for further studies on intra-tumoral heterogeneity in order to truly understand the genomic composition of any given tumor [ 5 ]. Such studies are critical to aid in our understanding of tumor and patient responsiveness and non-responsiveness to a range of therapies.…”
mentioning
confidence: 99%
“…Moon and Tompkins et al performed a comprehensive genomic analysis of multiple areas from within a single large MPNST. These authors identify varied genomic profiles within each area, highlighting the need for further studies on intra-tumoral heterogeneity in order to truly understand the genomic composition of any given tumor [ 5 ]. Such studies are critical to aid in our understanding of tumor and patient responsiveness and non-responsiveness to a range of therapies.…”
mentioning
confidence: 99%
“…Other studies have identified an increase in histone posttranslational modifications like H3K27Ac and H3K36me3 along with a global increase in DNA methylation levels in MPNST [84], but the chromatin regions undergoing this epigenetic reordering are reported for the first time in our study. A recent study has shown spatial heterogeneity of MPNST tumors by sampling multiple sites of same tumor [55]. Bulk sequencing approaches used in our study cannot identify this cellular heterogeneity and presents as a study limitation.…”
Section: Discussionmentioning
confidence: 79%
“…Resistant clonal populations within heterogeneous MPNSTs may explain the clinical failures of targeted kinase inhibitors in MPNSTs [ 44 ]. To determine if p53 is a key driver of clonal selection and drug resistance in MPNSTs, we performed a clonal competition assay using labeled isogenic NF1-MET-GFP and NF1-MET;sgP53-RFP cell lines.…”
Section: Resultsmentioning
confidence: 99%